2005
DOI: 10.2174/156802605775009739
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Metathesis Route to Antiviral Nucleosides

Abstract: The success of the early nucleoside agents, the toxicity and metabolic instability of many nucleoside analogues and the effects of viral pathogens on public health are driving the design, synthesis and evaluation of new nucleoside analogues. In this context, a powerful reaction has emerged over the past decade that has fundamentally changed the outlook on nucleoside chemistry: the olefin metathesis reaction. This review is designed to give an overview of the synthesis of some nucleosides of biological interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…chemistry would make their combination in cascade reactions a useful discovery. [70][71][72][73][74][75][76][77] In addition, evidence in the literature suggested that the Grubbs catalyst and MCPBA were incompatible. [78][79][80][81][82][83][84][85][86] In related work by others, it was shown that ruthenium compounds readily react with MCPBA to generate ruthenium oxo species.…”
Section: Resultsmentioning
confidence: 99%
“…chemistry would make their combination in cascade reactions a useful discovery. [70][71][72][73][74][75][76][77] In addition, evidence in the literature suggested that the Grubbs catalyst and MCPBA were incompatible. [78][79][80][81][82][83][84][85][86] In related work by others, it was shown that ruthenium compounds readily react with MCPBA to generate ruthenium oxo species.…”
Section: Resultsmentioning
confidence: 99%
“…The combination (o-tol) 3 P (L1)/PdA C H T U N G T R E N N U N G (OAc) 2 /Et 3 N (2:1 ligand/Pd stoichiometry) proved to be effective and was superior in reactivity to the well-defined Cat1. The role of additional L1 is currently unclear but the one example in Table 2 where equimolar amounts (10 mol% each) of L1 and PdA C H T U N G T R E N N U N G (OAc) 2 were used (entry 23) demonstrates that the additional equivalent of L1 is necessary, the absence of which led to retardation of the reaction. Scheme 2.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Table 2 is a listing of the most relevant results from this series of experiments. With iodobenzene, formation of the catalytic species from L1/PdA C H T U N G T R E N N U N G (OAc) 2 in situ proved to be superior to the use of Cat1 (entries 1 and 2 in Table 2). Although 31 P{ 1 H} NMR experiments have not provided insight into the observed differences in reactivity, it may be possible that the additional equivalent of L1 is not simply a bystander (see below).…”
Section: Entry Substratementioning
confidence: 99%
See 2 more Smart Citations